DC Electric pump modified as an intelligent actuator - Barbosa Torres, Alex Esteban; Escobar Díaz, Andrés; Vacca González, Harold (Ingeniería Solidaria, 2019)
Introduction: This paper describes the research – developed in 2007 by ORCA and SciBas – that modifies an actuator device (AD) – DC electric pump – making it Smart. Problem: There are currently no intelligent ADs of open architecture with the possibility of being easily manipulated in didactic plants. Objective: To identify and implement circuits to control an AD with signals. Methodology: The AD is developed following the family-standard IEEE 1452: implementing communication interfaces that characterize intelligent transducers connected to systems based on microprocessors, instruments and networks. The integration is made in a configuration platform that displays, records and manipulates AD information through a PC. Results: Obtaining a low-cost system based on Raspberry Pi - as an intelligent core - where the following are integrated: a PSOC 4 microcontroller to interact with the signals of the actuator, a circuit to manage the energy between the pump and the microcontroller, and an integrated signal that goes to a processor Originality: Modify a DC electric pump -as part of a didactic plant system- to have an intelligent AD architecture. The checking of filling and flow rates indicate advantages over traditional instrumentation: noise immunity, effective isolation of circuits from sources, work sequences, effective storage of actuator information, simple calibration, ease of signal transmission and remote control, and the possibility of intelligent presentations. Limitations: In non-didactic plants it is necessary to extend the research to the industrial sector and increase the quality of the elements. Introducción: El presente artículo describe la investigación —desarrollada en 2017 por ORCA y SciBas— que modifica un dispositivo actuador (DA) —electrobomba DC— haciéndolo inteligente. Problema: No se tiene un DA inteligente de arquitectura abierta con la posibilidad de ser manipulado sencillamente en plantas didácticas. Objetivo: identificar e implementar circuitos para controlar un DA con una señal. ...